SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI SMP BOPKRI 5 KEDUNG PENJALIN JEPARA - Isabela, Putri Cintia; Setianti, Novita; Sulistyasni, Sulisyasni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STMIK Widya Utama, 2024)
School libraries play an important role in supporting the teaching and learning process by providing various information resources. However, manual library management at SMP BOPKRI 5 Kedung Penjalin, Jepara, often faces challenges such as errors in recording, data management, and report generation. To address these issues, a web-based library information system was developed with the aim of improving efficiency and accuracy in library management. The system was developed using the Waterfall method, with testing conducted through two approaches: Black Box Testing and the System Usability Scale (SUS). The results of the Black Box testing showed that all features functioned according to the specifications. Meanwhile, SUS testing, involving 12 respondents from the school staff, yielded an average score of 79.4, categorized as